Reconstructing food colorants via synthetic biology: From microbial cell factories to sustainable biomanufacturing supply chains - Zeyu Li; Jiali Zhang; Junsong Xiao; Yingying Zhu; Dawei Ni; Wanmeng Mu (Food Research International, 2026)

Transcriptional and translational optimization for enhancing β-galactosidase expression in bacillus subtilis - Zhuo Cheng; Qiuzi Peng; Jiajun Chen; Li Wan; Dawei Ni; Wei Xu; Penka Petrova; Kaloyan Petrov; Wenli Zhang; Wanmeng Mu (Food Bioscience, 2026)

Acid-catalyzed ethanol pretreatment of sugarcane bagasse enables electrochemically improved hard carbon anodes for sodium-ion batteries - Nethmi Kulanika Dayarathne; Eric Campbell; Mu Xiao; Jiaye Ye; Cheng Yan; Hongxia Wang; Dawei Wang; Yu Lin Zhong; Zhanying Zhang (Chemical Engineering Journal, 2026)

Enhanced lactulose production by computer-aided design of cellobiose 2-epimerase - Zhaolin Huang; Wei Xu; Wenli Zhang; Aliaksandr Kastsianevich; Leanida Sapunova; Dawei Ni; Wanmeng Mu (Food Bioscience, 2026)

Enhanced levansucrase expression in Bacillus subtilis via regulatory element optimization for high-yield lactosucrose production from sucrose and lactose - Hangbin He; Yang Yang; Qiang Wei; Xiaoyong Liu; Wei Xu; Wenli Zhang; Dawei Ni; Wanmeng Mu (Bioresource Technology, 2026)

High-Efficiency N-acetylneuraminic acid biosynthesis in plasmid-free Escherichia coli MG1655 - Qian Lin; Yuanlin Liu; Wenbo Zhang; Liping Qiao; Yingying Zhu; Dawei Ni; Wanmeng Mu (Bioresource Technology, 2026)

Salinity and seasonal hydrological variability jointly shape the succession of groundwater microbial communities and ecological functions in irrigation districts - Dawei Mu; Peiyue Li; Bernard De Baets (Journal of Environmental Chemical Engineering, 2026)

Microbial and enzymatic strategies for aflatoxin control: Integrating intelligent detection and computational design - Binbin Ouyang; Wei Xu; Dawei Ni; Wenli Zhang; Junmei Ding; Wanmeng Mu (Food Chemistry, 2025)

Recent advances on health effects and biological production of functional monosaccharide d-mannose - Yehong Cao; Yihan Chen; Wei Xu; Yingying Zhu; Wenli Zhang; Dawei Ni; Wanmeng Mu (Trends in Food Science & Technology, 2025)

Wind-tide modulated net ecosystem metabolism in a Changjiang River Estuary aquaculture zone during mid-autumn - Di Wu; Kui Wang; Guoquan Wang; Qinglin Mu; Wei Fan; Dawei Xu (Marine Environmental Research, 2025)

Impacts of human activities on vegetation dynamics amid climate change: A case study of the Hanjiang River Basin (China) - Xiaofei Li; Peiyue Li; Meiling Gao; Dawei Mu; Dawei Han (Journal of Environmental Management, 2025)

Biogeochemical mechanisms and biomarkers of groundwater salinization in Jinghuiqu Irrigation District, China - Dawei Mu; Peiyue Li; Bernard De Baets (Journal of Environmental Management, 2025)

Fluoride enrichment in geothermal waters based on H, O, Sr, and Li isotopes of the Taiyuan Basin, North China - Chang Lu; Ying Li; Xiaocheng Zhou; Yuwen Wang; Weiye Shao; Zhaojun Zeng; Zhaofei Liu; Dawei Liao; Hui Zhang; Huimin Mu (Journal of Asian Earth Sciences, 2025)

Photothermal-Triggered Radical Storm for Achieving Multi-Layered PD-L1 Inhibition in Cancer Theranostics - Houren Zhou; Yiyong Tang; Hui Liu; Mengyao Mu; Shangui Liu; Yuan Gao; Kai Guo; Mengmeng Zhang; Nengyi Ni; Feifei Teng; Hongzan Sun; Dawei Chen; et al. (Chemical Engineering Journal, 2025)

The use of isomerases and epimerases for the production of the functional sugars mannose, allulose and tagatose from Fructose - Junya Yang; Yingying Zhu; Xu Wei; Dawei Ni; Wenli Zhang; Wanmeng Mu (World Journal of Microbiology and Biotechnology, 2025)

A comprehensive review on the properties, production, and applications of functional glucobioses - Shuqi Zhang; Dawei Ni; Yingying Zhu; Wei Xu; Wenli Zhang; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2024)

Application of molecular dynamics simulation in the field of food enzymes: improving the thermal-stability and catalytic ability - Zhaolin Huang; Dawei Ni; Ziwei Chen; Yingying Zhu; Wenli Zhang; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2024)

A multi-perspective exploration of the salinization mechanisms of groundwater in the Guanzhong Basin, China - Dawei Mu; Peiyue Li; Bernard De Baets; Dongfeng Li; Zhaoyu Li; Song He (Science of The Total Environment, 2024)

Directly mining and identifying a cellobiose 2-epimerase with isomerization activity by phylogenetic analysis - Zhaolin Huang; Binbin Ouyang; Jiajun Chen; Guocong Luo; Dawei Ni; Wei Xu; Wanmeng Mu (Food Bioscience, 2024)

Determining the Minimum Suitable Number of Water Quality Indicators to Improve the EWQI Water Quality Assessment Model in Baojixia Irrigation District, Northwest China - Dawei Mu; Jianhua Wu; Xiaomei Kou; Yong Wang (Exposure and Health, 2024)

Identification of a thermostable L-asparaginase from Pyrococcus yayanosii CH1 and its application in the reduction of acrylamide - Dawei Ni; Wei Xu; Wenli Zhang; Wanmeng Mu (Extremophiles, 2024)

Improving the activity of an inulosucrase by rational engineering for the efficient biosynthesis of low-molecular-weight inulin - Dawei Ni; Zhaolin Huang; Shuqi Zhang; Yang Yang; Xiaoyong Liu; Wei Xu; Wenli Zhang; Wanmeng Mu (Archives of Microbiology, 2024)

Sources and formation characteristics of particulate nitrate in the Pearl River Delta region of China: Insights from three-year online observations - Jisheng Zhang; Zheng Zong; Chenglei Pei; Qinyi Li; Liubin Huang; Jiangshan Mu; Yue Sun; Yuhong Liu; Haibiao Chen; Dawei Lu; Likun Xue; Wenxing Wang (Science of The Total Environment, 2024)

Spatiotemporal evolution of water resource sustainability in Shaanxi (China) from 2010 to 2020 based on an adapted water resources ecological footprint model - Xiaofei Li; Peiyue Li; Dawei Mu; Jifa Liu (Hydrological Sciences Journal, 2024)

Recent advances in discovery, protein engineering, and heterologous production of ketose 3-epimerase for rare sugar biosynthesis - Jiajun Chen; Dawei Ni; Wei Xu; Wenli Zhang; Wanmeng Mu (Trends in Food Science & Technology, 2024)

A review of fructosyl-transferases from catalytic characteristics and structural features to reaction mechanisms and product specificity - Wei Xu; Xiaoqi Zhang; Dawei Ni; Wenli Zhang; Cuie Guang; Wanmeng Mu (Food Chemistry, 2024)

Changes in Sea Level along the South China Sea Coast Based on the Homogenized Tide Gauge Data - Yan Li; Lin Mu; Dawei You; Jiaying Wang; Qianru Niu; Xiaomei Liao (Journal of Marine Science and Engineering, 2024)
To estimate the changes in the annual mean sea level (MSL) and extreme sea levels (ESLs), the largest collection of tide gauge records from 10 tidal stations along the northern coast of the South China Sea (SCS) were analyzed in this study. Here, all the tide gauge records had been homogenized by a two-step process involving the detection of inhomogeneities, that is, breakpoints caused by non-climatic changes and the application of the adjustment. The study’s conclusions, based on the homogenized tide gauge records, can be summarized as follows: The instrument change and station relocation are the main causes for the identified inhomogeneities. From 1989 to 2018, the sea level along the SCS was at an average rate of 4.0 mm per year, as measured by the homogenized tide gauges. The ESLs from the nine tidal stations rose notably with interannual fluctuations, except for the XSA station. Additionally, the ESLs exhibited substantial decadal variations. The ESLs rose along the northern coast of the SCS and were accelerated at most stations throughout the whole study period, especially after the 1980s. There were significant positive correlations between the ESL and the annual MSL at most tide gauges. The MSL’s changes, especially long-term changes, play an important role in the change in ESLs.

Microbial dextran-hydrolyzing enzyme: Properties, structural features, and versatile applications - Ziwei Chen; Jiajun Chen; Dawei Ni; Wei Xu; Wenli Zhang; Wanmeng Mu (Food Chemistry, 2024)

Production, effects, and applications of fructans with various molecular weights - Dawei Ni; Shuqi Zhang; Xiaoyong Liu; Yingying Zhu; Wei Xu; Wenli Zhang; Wanmeng Mu (Food Chemistry, 2024)

Identification and application of a novel deoxynivalenol-degrading enzyme from Youhaiella tibetensis - Yan Shi; Wei Xu; Dawei Ni; Wenli Zhang; Cuie Guang; Wanmeng Mu (Food Chemistry, 2024)

Recent progress in health effects and enzymatic production of epilactose, a functional lactose derivative - Suchun Xiong; Zhaolin Huang; Wei Xu; Junmei Ding; Dawei Ni; Wanmeng Mu (Trends in Food Science & Technology, 2024)

Modeling the effects of land use/land cover changes on river runoff using SWAT models: A case study of the Danjiang River source area, China - Weichao Liu; Jianhua Wu; Fei Xu; Dawei Mu; Pengbin Zhang (Environmental Research, 2024)

Identification of the Spatiotemporal Variability and Pollution Sources for Potential Pollutants of the Malian River Water in Northwest China Using the PCA-APCS-MLR Receptor Model - Dawei Mu; Jianhua Wu; Xiaofei Li; Fei Xu; Yongqiang Yang (Exposure and Health, 2024)

Unveiling the biogeochemical mechanism of nitrate in the vadose zone-groundwater system: Insights from integrated microbiology, isotope techniques, and hydrogeochemistry - Dan Wang; Peiyue Li; Dawei Mu; Weichao Liu; Yinfu Chen; Misbah Fida (Science of The Total Environment, 2024)

Groundwater Quality Assessment Using EWQI With Updated Water Quality Classification Criteria: A Case Study in and Around Zhouzhi County, Guanzhong Basin (China) - Yongqiang Yang; Peiyue Li; Vetrimurugan Elumalai; Jing Ning; Fei Xu; Dawei Mu (Exposure and Health, 2023)

Occurrence, functional properties, and preparation of 3-fucosyllactose, one of the smallest human milk oligosaccharides - Zeyu Li; Yingying Zhu; Dawei Ni; Wenli Zhang; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2023)

Infant formulae – Key components, nutritional value, and new perspectives - Guocong Luo; Yingying Zhu; Dawei Ni; Jiajun Chen; Wenli Zhang; Wanmeng Mu (Food Chemistry, 2023)

Spatial distribution, source apportionment and potential ecological risk assessment of trace metals in surface soils in the upstream region of the Guanzhong Basin, China - Linjie Xie; Peiyue Li; Dawei Mu (Environmental Research, 2023)

Engineering D-allulose 3-epimerase from Clostridium cellulolyticum for improved thermostability using directed evolution facilitated by a nonenzymatic colorimetric screening assay - Jiajun Chen; Zhaolin Huang; Ting Shi; Dawei Ni; Yingying Zhu; Wei Xu; Wenli Zhang; Wanmeng Mu (Food Bioscience, 2023)

Molecular characterization and expression analysis of hypoxia-inducible factor-1α, factor-2α, and factor-3α and physiological response to hypoxia exposure in Amur minnow (Phoxinus lagowskii) - Yuting Yang; Zhongdian Dong; Xi Chen; Zhen Wang; Dawei Zhang; Liqun Liang; Weijie Mu (Aquaculture International, 2022)

Recent advances on 2′-fucosyllactose: physiological properties, applications, and production approaches - Yingying Zhu; Li Wan; Wen Li; Dawei Ni; Wenli Zhang; Xin Yan; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2022)

Histopathological parameters, antioxidant enzyme levels, transcriptome, and hematology parameters of Amur minnow (Phoxinus lagowskii) infection with Tetrahymena pyriformis - Zhen Wang; Zhongdian Dong; Dawei Zhang; Liqun Liang; Weijie Mu (Aquaculture International, 2021)

Recent advances in Levansucrase and Inulosucrase: evolution, characteristics, and application - Wei Xu; Dawei Ni; Wenli Zhang; Cuie Guang; Tao Zhang; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2019)